Coping with Policy Paradoxes and Actor Interests in Peatland and Oil Palm Management in Indonesia - Purwanto, Erwan Agus (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
The utilization of peatland is one of the important issues in Indonesian political economy. One of the pros and cons regarding the argument of peatland management is the problem of ecology, which refers to the involvement of actors in its policy formulation and implementation. Research found that extensive degradation of Indonesia peatlands by deforestation, drainage and recurrent fires causes the release of huge amounts of peat soil carbon into the atmosphere. This article aims to answer two research questions. First is related to problems arise from the management of peatland based on ecological, economic, and social-cultural perspective. Second is related to the interests of actors in the management of peatland in Indonesia. As a result, there are several numbers of problems that appeared, due to the lack of understanding peatland management, such as environmental damage, labor exploitation, policy ambiguity. There are paradoxes in government policies pertaining to peatland management, as its implementation bears massive impact on the industry which consequently influences the production process. Furthermore, numerous actors also involved in this issue and policy accommodating the interests of each actor is a necessity.